(3efJNH ef cJGH CfhGQ GdLhGgQ hGddBdi aj CSQGQ GdeYOf GdYGdis
(3ChdgG (B:s
(3GYde Gf eHfi CUhd GdMceGA GdSCdag Ydi Cf GdefRdg GdChdi ef efGRd GdbeQ s
(3BNQgG (B:s
(3EdGeG CLHJe haYdJe cPG hcPG (B( (3HYOgG CSeGA jSJYedgG GdQhMGfjjf ai JYGhjPge (B) s
(3ai hUa efGRd GdbeQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B101 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3Gdadcs